English-Indonesian Translation Of Existential Sentences Found In The Intelligent Investor (e-Journal of Linguistics, 2019)
This study investigated English-Indonesian translation of existential sentence. It aimedat (1) Identifying the way of translating English existential sentences into Indonesian and (2)Investigating kinds of translation shift found in the translation of English existential sentencesinto Indonesian. Existential sentence is a non-canonical sentence used to express the existence ofsomething or someone marked by dummy subject there and copula be. Here, the Englishexistential sentences were translated into the inversion structure in Indonesian with V-NP wordorder. The structure preserved the existential content by placing Indonesian existential verbs inthe initial position of the sentences, there were two most frequently used verbs, those are ada andterdapat. Both verbs can be substituted to present the same ideas. Since English and Indonesianhave different language structure, translation shift in term of structure shift was found intranslating existential sentences from English into Indonesian.
Keywords: translation; existential sentence; translation shift